(untitled) (Journal of Health, Population and Nutrition, 2011)
Stunting adversely affects the physical and mental outcome of children. The objectives of the study were to determine the prevalence of and risk factors associated with stunting among urban school children and adolescents in Abeokuta, Nigeria. Five hundred and seventy children aged 5-19 years were selected using the multi-stage random-sampling technique. Stunting was defined as height-for-age z-score (HAZ) of <-2 standard deviation (SD) of the National Center for Health Statistics reference. Severe stunting was defined as HAZ of <-3 SD. The mean age of the children was 12.2+3.41 years, and 296 (51.5%) were males. Ninetynine (17.4%) children were stunted. Of the stunted children, 20 (22.2%) were severely stunted. Identified risk factors associated with stunting were attendance of public schools (p<0.001), polygamous family setting (p=0.001), low maternal education (p=0.001), and low social class (p=0.034). Following multivariate analysis with logistic regression, low maternal education (odds ratio=2.4; 95% confidence interval 1.20- 4.9; p=0.015) was the major contributory factor to stunting. Encouraging female education may improve healthcare-seeking behaviour and the use of health services and ultimately reduce stunting and its consequences. Key words: Adolescent; Child; Child nutrition disorders; Community-based studies; Cross-sectional studies; Nutrition disorders; Risk factor; Stunting; Nigeria DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8452 JHPN 2011; 29(4): 364-370